Introduction of a Protestant Choral Music Method to Melbourne’s Jewish Community:: Raphael Benjamin and Joel Fredman (Journal of Music Research Online, 2022)
One of the principle methods of teaching vocal music literacy during the nineteenth century in Britain was John Curwen’s Tonic Sol-fa. The original aim of the method was to provide a simple means of promoting Sunday School singing and it soon became the medium for hymn singing in Protestant churches, in community choral singing and later in school music education. In contrast to Orthodox Judaism, Jewish communities in England were influenced by the Jewish Reform Movement and a distinctive form of Anglo-Judaism emerged which gave greater prominence to music within the synagogue worship. The majority of Jews emigrating to Australia from England at this time were influenced by the Anglo-Judaic religious practices which reflected a certain degree of ‘protestantisation’. This article describes one such aspect of Protestantism, Tonic Sol-fa, introduced to the Melbourne Hebrew Congregation, then located in Bourke Street, and to the St Kilda Hebrew Congregation in Charnwood Grove. The two choirmasters at these synagogues, Raphael Benjamin (1846–1906) at Melbourne and Joel Fredman (1860–1943) at St Kilda, were proponents of Tonic Sol-fa and trained their choral singers in its use. They were also enthusiastic supporters of the Victorian Tonic Sol-fa Association and advocated use of the method and its letter notation in Victorian State Schools. It is maintained that the assimilation of Tonic Sol-fa into Melbourne’s Jewish musical culture and the contributions by Benjamin and Fredman to synagogue music during the late nineteenth and early twentieth centuries laid down a solid musical foundation for these two communities.